All under heaven KANO: The politics of nostalgia and the making of a new Taiwanese identity in Wei Te-sheng's Taiwan-Japan trilogy. Issue 2 (1st August 2017) - Green, Frederik H.
This article explores the highly contested topic of nostalgia for the Japanese colonial period in contemporary Taiwanese popular culture and the ways in which colonial nostalgia participates in contemporary identity politics in Taiwan. By analysing three of Wei Desheng's recent movies that engage in different ways with aspects of the colonial past, this article illustrates how the creative use of nostalgia helps to challenge certain cultural and political narratives that have hitherto dominated discourses of identity in Taiwan. Focusing in particular on Wei's baseball period-drama KANO, this study shows that nostalgia in Taiwanese cinema is not a singular trope whereby the bygone colonial era is uncritically eulogized, but a complex cultural practice through which issues such as Taiwan's position in a globalizing economy, a new emphasis on diversity and multi-culturalism, and finally contemporary politics vis-à-vis mainland China are negotiated. The colonial past, far from being a stable, monolithic historical memory, thus constitutes a constantly shifting discursive space in which questions of national identity can be addressed from a number of angles.